The Effects of Leverage and Profitability on Tax Aggressiveness, Moderated by Good Corporate Governance in Manufacturing Companies - Syalita Amalia Faatihah; Murtianingsih (Proceeding Economy of Asia International Conference, 2026)
Introduction: Income tax is an obligatory expenditure for corporate entities, which contradicts the primary purpose of profit maximization.This encourages companies to adopt assertive tax evasion tactics. This study examines the moderating influence of independent commissioners on the association between leverage (DAR) and profitability (ROA) and tax aggressiveness (ETR). Background Problems: Leverage and profitability are often regarded as significant determinants of tax aggression; nevertheless, empirical evidence regarding their correlation has been inconclusive. Therefore, this study seeks to answer whether independent commissioners can moderate the association between leverage, profitability, and tax aggressiveness. Novelty: The use of independent commissioners as a moderating variable is the unique aspect of this study, which aims to rectify the inconsistencies found in previous empirical findings regarding leverage, profitability, and tax aggressiveness. Research Methods: This research employs a quantitative approach to examine secondary data with SPSS version 26. The population includes manufacturing firms registered on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Ninety-six data points were acquired from the food and beverage sub-sector using purposive sampling, following the exclusion of outliers. The approach encompasses traditional assumption testing and Moderated Regression approach (MRA). Finding/Results: The results demonstrate that leverage and profitability exert no substantial partial influence on tax aggression. Independent commissioners, however, moderate the association between leverage and tax aggression. While leverage and profitability do not directly and significantly influence tax aggressiveness, effective Corporate Governance (indicated by independent commissioners) amplifies the leverage effect on tax aggressiveness. The research model accounts for merely 10.8% of the variance in tax aggression. Conclusion: The findings indicate that leverage and profitability have no substantial impact on tax aggressiveness. However, independent commissioners strengthen the connection between leverage and tax aggressiveness.